2016
DOI: 10.1016/j.alit.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Problems of elderly patients on inhalation therapy: Difference in problem recognition between patients and medical professionals

Abstract: Elderly patients are apt to assume that they "understand well", therefore, in order to recognize and close the perception gap between elderly patients and medical professionals, it is necessary to provide them with more aggressive (frequent) instructions on inhalation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…15 It has been reported that an inhaled medicine has significantly lower adherence than a transdermal patch. 16 Similarly, this study showed that adherence was lower for inhaled agents than for oral agents or transdermal patches. In addition, erroneous operation is often a problem with inhaled medicines.…”
Section: Dovepressmentioning
confidence: 57%
“…15 It has been reported that an inhaled medicine has significantly lower adherence than a transdermal patch. 16 Similarly, this study showed that adherence was lower for inhaled agents than for oral agents or transdermal patches. In addition, erroneous operation is often a problem with inhaled medicines.…”
Section: Dovepressmentioning
confidence: 57%
“…Inhalation instruction plays an important role in inhalation therapy for asthma and COPD because therapeutic efficacy of inhalation medicine is influenced by the patient’s inhalation technique [ 3 , 30 33 ]. Therefore, it is an urgent issue to develop inhalation instruction tools for a large variety of inhalation devices [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] We decided to use 70 years as the cutoff age to determine inhalation understanding. [25] The translated (from Japanese) parameters of the guidance sheet included the following: Guidance was provided through multiple outpatient open pharmacies. At each visit, the patient received practical guidance from the pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…[ 23 , 24 ] We decided to use 70 years as the cutoff age to determine inhalation understanding. [ 25 ]…”
Section: Methodsmentioning
confidence: 99%